Wernicke's Encephalopathy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1988)
Two cases of Wernicke's encephalopathy (WE) diagnosed at autopsy are reported from the Depts of Pediatrics and Pathology, British Columbia's Children's Hospital, and the University of British Columbia, Vancouver, Canada.